Perhitungan Rasio Keuangan sebagai Alat Penilaian Tingkat Kesehatan pada Koperasi Perbaikan Masyarakat Wanita (Permata) Kabupaten Kuningan - Unsriyani, Enci; Irawan, Arry (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This research was conducted at the Women's Community Improvement Cooperative (Permata) Kuningan Regency. The research purpose is to determine the results of financial performance at Permata Cooperative. The research method is descriptive quantitative with data collection techniques using interviews and documentation. Data source used comes from Permata Cooperative's financial statements for 2016-2020. Based on the results for capital aspect, Permata Cooperative obtained total score of 10.50 points with predicate